A Crusading Voice for the Mining West: How the Rossland Evening World Served Militant Workers at the Turn of the 20th Century - Verzuh, Ron (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
The Rossland Evening World, a four-page daily dedicated to the mineworkers of British Columbia’s bustling West Kootenay mining town of Rossland, first appeared on May Day 1901 – just in time to do battle with local mine owners in the historic 1900–01 miners’ strike. The World may have owed its existence in part to William “Big Bill” Haywood, a founder of the militant Western Federation of Miners (wfm) and the Industrial Workers of the World. On visiting the town and the prospectors’ camp in the 1890s, Haywood saw that Rossland would soon grow into a thriving Pacific Northwest mountain community with a steady increase in wfm membership. He encouraged the miners to form wfm Local 38, possibly the first wfm local in Canada, and soon a dozen Kootenay locals formed wfm District Association 6. A wfm grant followed to help launch the local and the new daily. Amid growing frustration with bad working conditions and mine owners’ refusal to recognize the wfm, the World became a welcome sister to the wfm’s Miners’ Magazine, dedicating itself to “the Interests of Organized Labor.” By the fall of 1900, the strike of 1,400 miners was on, and the World published news and analysis throughout the region. Ultimately the strike was lost, but the World carried on until 1904. As its legacy, it showed how a daily newspaper could help build community support and provide a defence for the local unionized workforce.